Effect Of Compensation And Work Discipline On The Performance Of Production Section Employees At PT. Daiwani Putra Main: - Hayat, Munawar Bahrul; Karmila, Mila; Oktaviani, Nita Fauziah (Jurnal Pusat Manajemen, 2024)
This research took place in Tasikmalaya City and aims to determine the effect of compensation and work discipline on employee performance production department at PT. Daiwani Putra Utama. This research involves use of survey methods with a quantitative approach, employee section production as a population, and random sampling techniques with cluster sampling as a sampling technique with a sample size of 55 people production employees. Data processing is carried out from primary data sources and and secondary. The research data is then processed by testing validity and reliability, classical assumption tests, statistical analysis tests, and hypothesis tests with using the SPSS version 25 application. Based on the F test results, it shows compensation and work discipline influence employee performance significantly. The T test results show that compensation partially influences performance employees significantly, while work discipline partially does not significantly affects employee performance.